PEMBUATAN PROGRAM SISTEM PENJUALAN HELM BERBASIS WEB PADA TOKO HELM KARTINI - Donni Kurniawan; Ery Dewayani (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
Helmet Sales System Program at the Kartini Helmet Shop, located in Bekasi City, aims to create a helmet sales program in the form of a website that can process transactions online. Customers can process orders, payments and deliveries online through the helmet sales website which is opened with a web browser. Store owners can print sales reports to see the results of their product sales, customer reports to see customers who bought the most and financial reports to see revenue earned. In making this program using the Waterfall method. In designing this program using Context Diagrams, Data Flow Diagrams, Entity Relationship Diagrams, Relationships Between Tables and Table Specifications. The programming languages used in making this program are HTML and PHP with the CodeIgniter Framework and use the MySQL database.